Penglipuran Tourism Village, Kubu Village, Bangli District, Bali In Maintaining Bali Local Wisdom Values - I Wayan Wesna Astara; Nyoman Putu Budiartha; Putu Ayu Sriasih Wesna; I Ketut Selamet; I Kadek Merta Wijaya (Journal of Legal and Cultural Analytics, 2023)
Development of the Penglipuran tourism village based on Balinese local wisdom is a solution to the settlement of AYDs land cases in the Penglipuran Traditional Village in the legal and cultural context associated with Law Number 10 of 2009 concerning tourism-related to the issuance of Bali Province Regional Regulation No. 5 of 2020 regarding standards for the implementation of Balinese cultural tourism. Article 1, paragraph b, Tourism Village However, ideologically, culturally, and legally, there is a hidden potential for conflict. The problem of tourist villages can be solved using absorption methods from research results to provide solutions for managing tourist villages. The methods used in legal issues in the management of tourism villages include focus group discussions, mentoring, lectures on legal studies, dissecting cases related to tourism village institutions, and finding potential strategies for Balinese local wisdom to strengthen wisdom-based tourism villages